PERKEMBANGAN PERTENTANGAN HUKUM SEBAGAI SUATU SISTEM DALAM PERSPEKTIF PENEGAKAN HUKUM DI INDONESIA - Ariya Zurnetti dan Himawan Ahmed Sanusi (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
The law can assessed by utilizing four main approaches, namely the philosophical approach, philosophy of law science, philosophical law, scientific legal approach. The development of the law of a state as a system will be influenced by the development of system theory and history in society. The question is how to develop the legal contradiction as a system in the perspective of law enforcement in Indonesia. So that can be found in the form of five things contradictions about the concept of law system. In the law enforcement perspectives of Indonesia based on expert opinion (theoretical studies) and the development of community life.